Has The Teacher Taught Chemical Literacy? A Phenomenological Qualitative Research - Suparman, Achmad Rante (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
Chemical literacy consists of understanding chemical properties, theory, chemistry, and the nature of chemical phenomena. Proficiency in chemical literacy is fundamental in obtaining basic chemistry concepts, such as chemical interactions at the microscopic, macroscopic, symbolic, and process levels, and understanding and describing phenomena scientifically. Chemical literacy is critical in the learning process at school; therefore, teaching and learning should focus on chemical literacy. This study aims to determine whether teachers have taught chemical literacy in schools. This research is phenomenological qualitative research. Data collection techniques through natural conditions, primary data sources, in-depth interviews, documentation, and participatory observation techniques. The study participants were 24 chemistry teachers: eight on Papua Island representing eastern Indonesia, eight on Sulawesi Island representing central Indonesia, and eight on Java representing western Indonesia. Data were analyzed using the Bogdan and Biklen model. The results showed that the Teacher had yet to teach chemical literacy, although, in the learning process, several principles of chemical literacy had been implemented